Multi-omics dissection of metabolic dysregulation associated with immune recovery in people living with HIV-1 - Lin-Yu Wan; Sin Man Lam; Hui-Huang Huang; Wen-Jing Cao; Xiang-Yi Cao; Xue-Meng Li; Li-Ping Zhang; Jia-Min Gao; Chao Zhang; Xing Fan; Yan-Mei Jiao; Guanghou Shui; et al. (Journal of Translational Medicine)
Abstract Background Despite the success of antiretroviral therapy (ART) in suppressing HIV-1 replication, some people living with HIV-1 (PLWH) fail to achieve an optimal recovery of CD4 T cells, and precise metabolic regulation underlying immune recovery remained poorly understood. Methods In this cross-sectional study, mass spectrometry was used for quantitative analysis of plasma metabolome and lipidome in 24 treatment-naïve PLWH (TNs), 33 immunological responders (IRs), 35 immunological non-responders (INRs), and 16 healthy controls (HCs). The data were analyzed using the Mann–Whitney U-test, Kruskal–Wallis test, Spearman correlation, and LASSO regression analysis. Results Significant metabolic dysregulation was observed in TNs, IRs and INRs compared to HCs. In TNs, metabolomic analysis revealed increased levels of 3-hydroxyoctanoic acid, 3-oxododecanoic acid, 5-hydroxy-L-tryptophan, 5-hydroxyindoleacetic acid, L-kynurenine, oleoylcarnitine, and pseudouridine that were positively correlated with CD8 T cell activation and inflammation-related markers, and decreased levels of phosphorylcholine, ribothymidine, and thymine that were negatively correlated. Notably, 3-hydroxyoctanoic acid and thymine were consistently associated with CD4 T cell counts and inflammation-related markers in PLWH, regardless of ART. Pathway analysis uncovered the biosynthesis of unsaturated fatty acids as the major dysregulated pathway in TNs, IRs, and INRs, while primary bile acid biosynthesis was the dysregulated pathway specifically in INRs. Lipidomic analysis indicated higher plasma triacylglycerols, free fatty acids, ceramide, and monosialodihexosyl gangliosides (GM3) in TNs, IRs, and INRs compared to HCs. Pathway enrichment and differential correlation analyses underscore perturbed systemic lipid metabolism in treatment response to ART, possibly mediated by host-commensal metabolic interactions. Ultimately, we identified two panels, one consisting of 9 metabolites and another of 8 lipids, that can effectively distinguish INRs from IRs. Conclusions Metabolic aberrations induced by chronic HIV-1 infection persist and do not recover with ART. Abnormal primary bile acid biosynthesis pathway and levels of DHA-containing lipids are closely associated with CD4 T cell recovery. These finding provide new intervention targets to achieve better immune recovery in PLWH.